2016
DOI: 10.1111/1365-2745.12609
|View full text |Cite
|
Sign up to set email alerts
|

Plant mutualisms with rhizosphere microbiota in introduced versus native ranges

Abstract: Summary1. The performance of introduced plants can be limited by the availability of soil mutualists outside their native range, but how interactions with mutualists differ between ranges is largely unknown. If mutualists are absent, incompatible or parasitic, plants may compensate by investing more in root biomass, adapting to be more selective or by maximizing the benefits associated with the mutualists available. 2. We tested these hypotheses using seven non-agricultural species of Trifolium naturalized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 78 publications
2
30
0
Order By: Relevance
“…Although the richness of rhizobia strains associated with some species of NZ‐naturalised Trifolium has been shown to be comparable to strain richness in the UK (McGinn et al., ), the effectiveness of rhizobia strains at fixing nitrogen can differ between the introduced and native ranges of legume species (Parker, Wurtz, & Paynter, ), and this could affect the strength and direction of PSF. Indeed, in our previous study, we found that growth rates of some Trifolium species as a factor of rhizobia colonisation were higher when plants were grown in soil from their native range relative to their introduced range (Shelby, Duncan, et al., ). We therefore developed a method to statistically remove the influence of rhizobia on plant growth in order to focus on the effects of other soil biota, such as soil‐borne antagonists and AMF, on plant performance.…”
Section: Methodsmentioning
confidence: 87%
“…Although the richness of rhizobia strains associated with some species of NZ‐naturalised Trifolium has been shown to be comparable to strain richness in the UK (McGinn et al., ), the effectiveness of rhizobia strains at fixing nitrogen can differ between the introduced and native ranges of legume species (Parker, Wurtz, & Paynter, ), and this could affect the strength and direction of PSF. Indeed, in our previous study, we found that growth rates of some Trifolium species as a factor of rhizobia colonisation were higher when plants were grown in soil from their native range relative to their introduced range (Shelby, Duncan, et al., ). We therefore developed a method to statistically remove the influence of rhizobia on plant growth in order to focus on the effects of other soil biota, such as soil‐borne antagonists and AMF, on plant performance.…”
Section: Methodsmentioning
confidence: 87%
“…Recent work has detected substantial differences in nodule rhizobial communities in the native and non-native ranges of some legumes (e.g. Callaway et al, 2011;Shelby et al, 2016). In these instances, mutualism establishment in the non-native range probably did not involve co-introduction of rhizobia.…”
Section: Review 1355mentioning
confidence: 99%
“…In support of novel associations, recent molecular research has demonstrated unique rhizobial communities in association with some legumes in their native versus non-native ranges (e.g. Birnbaum, Barrett, Thrall, & Leishman, 2012;Callaway, Bedmar, Reinhart, Silvan, & Klironomos, 2011;Shelby et al, 2016).…”
Section: Introductionmentioning
confidence: 99%